Development and Validation of Pediatric Opioid Analgesia Self-Instruction System (PedOASIS): An Opioid Knowledge Tool for Pediatric Clinicians. Issue 1 (13th August 2021) - MacDonell-Yilmaz, Rebecca E.; Anderson, Angela; Hirway, Priya; Welch, Jennifer G.
Abstract : Background: Acute pain is common in children and young adults with cancer and sickle cell disease. Current training curricula fail to adequately impart skills for pain management. We sought to develop and validate an education and assessment tool to address the safe effective use of opioids for pain management by pediatrics trainees. Methods: The first version of the tool contained 10 case-based, multiple-choice questions. It was pilot tested within a medium-sized pediatric residency program using preintervention and postintervention surveys to assess residents' knowledge and comfort related to prescribing opioids. Content validation was performed through an expert panel of physicians. Internal reliability was tested by administering the tool to learners and practitioners with varying levels of training. Results: Comfort with choosing and converting between opioids increased significantly in pilot testing ( P =0.005). Mean objective knowledge scores increased from 51% to 85.9% ( P <0.001). The revised tool showed internal reliability within each group (Cronbach alpha 0.71 to 0.78) and significant differences in mean scores between groups ( F ratio=9.45, P =0.0002). Conclusions: This tool demonstrates validity and internal reliability. Its use was associated with short-term educational gains and it garnered overall favorable feedback from users. Further testing is needed to assess the duration of these gains.